Biosafety and biosecurity practical insights and applications for low and medium-income countries - Guerrero, Jonathan Jaime G.; Cena-Navarro, Rohani; Destura, Raul V.; De Leon, Marian P.; Notarte, Kin Israel R.; Balendres, Mark Angelo O. (Boca Raton, FL CRC Press, 2025)
This book provides a comprehensive summary of the state and development of biosafety and biosecurity in developing and developed nations in a comparative analysis. It includes basic concepts and principles of biosafety and biosecurity, including certification and legal frameworks across disciplines including environmental, medical, and special topics that are relevant to countries with comparable conditions. This proposed book solves the problem of the lack of a prescribed professional title that comprehensively summarizes the state and development of biosafety and biosecurity throughout the world, allowing the reader a 360 view of the subject area"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Biosecurity -- Developing countries; Communicable diseases -- Prevention; Biological laboratories -- Developing countries -- Safety measures